Hubungan Frekuensi Makan dan Pola Istirahat dengan Produksi Asi pada Ibu Nifas - Christina Nur Widayati; Yuwanti Yuwanti; Rizki Sahara (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2020)
Breast milk is an emulsion of fat in a solution of protein, lactase and organic salts secreted by the two sides of the mother's breast glands, as the main food for the baby. Post-partum mothers who produce little breast milk will interfere with the adequacy of the baby's needs during their growth and development. The purpose of this study was to determine the relationship between eating frequency and resting patterns with mother's milk production during the postpartum period in the village of Kontak Grobogan. This research method using analytical method with cross sectional approach. The sample in this study amounted to 31 people. The analytical test for the research hypothesis used the Chi Square test. The results of this study show that mothers who consume food frequently are 38.7%, and mothers who have good resting patterns have sufficient milk production as much as 14.3%. The results of the analysis using Chi Square with Î± = 0.05 on the frequency of eating with breast milk production found a p value = 0.092, while the resting pattern with breast milk production is known to have a p value = 0.241. It can be concluded from this study that the frequency of eating is not related to the production of breast milk in the mother, and the resting pattern is also not related to the production of breast milk in the mother during the postpartum period.